Comparative Study of DNA Extraction Methods for Halal Food Testing: Advantages, Disadvantages, and Recommended Methods - Citra Yulia Sari; Raditya Yudhi Pamungkasa; Setiyo Gunawan (Halal Center ITS, 2025)
Identification of the halal status of food is a crucial aspect of the food industry, particularly in countries with a majority Muslim population. DNA extraction methods play a critical role in ensuring the halal status of food products by accurately detecting nonhalal substances. This study conducted a comparative evaluation of various DNA extraction methods used in halal food testing. We reviewed several DNA extraction methods listed in RSNI3 ISO 21571:2005 titled